Salt marsh ecosystem restructuring enhances elevation resilience and carbon storage during accelerating relative sea-level rise. (5th February 2019) - Gonneea, Meagan Eagle; Maio, Christopher V.; Kroeger, Kevin D.; Hawkes, Andrea D.; Mora, Jordan; Sullivan, Richard; Madsen, Stephanie; Buzard, Richard M.; Cahill, Niamh; Donnelly, Jeffrey P.
Abstract: Salt marshes respond to sea-level rise through a series of complex and dynamic bio-physical feedbacks. In this study, we found that sea-level rise triggered salt marsh habitat restructuring, with the associated vegetation changes enhancing salt marsh elevation resilience. A continuous record of marsh elevation relative to sea level that includes reconstruction of high-resolution, sub-decadal, marsh elevation over the past century, coupled with a lower-resolution 1500-year record, revealed that relative sea-level rose 1.5 ± 0.4 m, following local glacial isostatic adjustment (1.2 mm/yr). As sea-level rise has rapidly accelerated, the high marsh zone dropped 11 cm within the tidal frame since 1932, leading to greater inundation and a shift to flood- and salt-tolerant low marsh species. Once the marsh platform fell to the elevation favored by low-marsh Spartina alterniflora, the elevation stabilized relative to sea level. Currently low marsh accretion keeps pace with sea-level rise, while present day high marsh zones that have not transitioned to low marsh have a vertical accretion deficit. Greater biomass productivity, and an expanding subsurface accommodation space favorable for salt marsh organic matter preservation, provide a positive feed-back between sea-level rise and marsh platform elevation. Carbon storage was 46 ± 28 g C/m 2 /yr from 550 to 1800 CE, increasing to 129 ± 50 g C/m 2 /yr in the last decade. Enhanced carbon storage is controlled by vertical accretion rates, rather than soil carbon density, and is a direct response to anthropogenic eustatic sea-level rise, ultimately providing a negative feedback on climate warming. Graphical abstract: Highlights: New England salt marshes transition from high to low marsh habitat under the highest rates of sea-level rise in 1500 years. Low marsh transgression results in resilient platform elevation due to greater productivity and organic matter accretion. Accelerating accretion in response to sea-level rise results in enhanced carbon storage rates in salt marshes.